The impacts of climate change policies on the transportation sector - Solaymani, S.; Kardooni, R.; Yusoff, S.; Kari, F. (Elsevier, 2015)
This study examines the impact of carbon tax and its alternative, energy tax, on both the Malaysian economy and the transport sector, using a CGE (Computable General Equilibrium) framework. In order to achieve government revenue neutrality, two schemes for revenue recycling, namely lump-sum transfer and labour tax recycling, are employed. The simulation's results show that the carbon tax policy is more effective than the energy tax policy in reducing carbon emissions; because it is less expensive. The negative impact of the carbon tax, on real GDP (Gross Domestic Product) and investment, is less than the energy tax in both recycling schemes. Through lump-sum transfer, both taxes lead to an increase in the consumption and welfare of households, because the tax interaction effect is less than the tax recycling effect; however, through labour tax recycling, they decrease the consumption and welfare of all household groups. These tax policies are not beneficial for the transportation sector, because they lead to decreases in domestic output, domestic demand, exports and imports of all transport sectors. The climate change policies would lead to mitigation of rebound effect in whole of the economy and the transport sector. (C) 2015 Elsevier Ltd. All rights reserved.